2017
DOI: 10.4236/ojn.2017.77054
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Rural Emergency Department Providers regarding Telehealth-Based Care: Perceived Competency, Satisfaction with Care and Tele-ED Patient Disposition

Abstract: Introduction: This study assesses rural providers' perceptions of their ability to deliver high quality care via telehealth compared to usual care, and whether attending providers perceive that emergency department (ED) telehealth visits influence clinical reasoning in regard to patient disposition, specifically in tele-behavioral and tele-neurological cases. Methods: A cross-sectional survey was conducted of 134 ED providers (nurses [n = 126] and physicians [n = 8]) who were working in five Midwestern critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…While our quality of care findings align with some previous literature, 13 care teams in the current analysis overwhelmingly would recommend telemedicine, whereas some clinicians in prior work would not recommend telemedicine. 14 In terms of communication, in line with existing literature, some patients still preferred in-person visits, 15 a view also shared by some care team members. Workflow and technology barriers were raised, corroborating existing work, 13 but actionable solutions (eg, adding care team-only time before visits or verbalizing when to move stethoscopes) were also identified.…”
Section: Resultsmentioning
confidence: 55%
“…While our quality of care findings align with some previous literature, 13 care teams in the current analysis overwhelmingly would recommend telemedicine, whereas some clinicians in prior work would not recommend telemedicine. 14 In terms of communication, in line with existing literature, some patients still preferred in-person visits, 15 a view also shared by some care team members. Workflow and technology barriers were raised, corroborating existing work, 13 but actionable solutions (eg, adding care team-only time before visits or verbalizing when to move stethoscopes) were also identified.…”
Section: Resultsmentioning
confidence: 55%
“…The evaluation and outcomes of the participating rural ED health care provider teams have been reported elsewhere in relationship to perceptions of (1) their competency level, (2) the study's telehealth equipment, and (3) the implementation process in the participating rural EDs. 20 Initial feedback provided by the ED health care provider teams during 2015 included the following: (1) poor internet connectivity and (2) cumbersome equipment that was too prone to breakage for telebehavioral visits.…”
Section: Study Protocolmentioning
confidence: 99%
“…Recognizing that EM telehealth is relatively new, there is a need for evaluation studies of EM health care professionals' perception to validate and gain acceptance as part of EM practice. [15][16][17] In 2016 the American College of Emergency Physicians (ACEP) indicated that, with regard to telehealth, "an appropriate and adequate examination to establish a diagnosis or underlying condition" should be performed. 18 Further, the "technology used must be adequate to enable an examination similar to that possible in a face-toface encounter."…”
Section: Competenciesmentioning
confidence: 99%